Tracing the 'grey literature' of poster presentations: a mapping review. (6th April 2017) - Rowe, Nicholas
Abstract: Background: Posters are a popular way of presenting information at conferences. However, little research has been conducted into their development, and the patterns and extent of their use are unclear. Objectives: A mapping review was performed to chart the development and utilisation of the poster medium, and to highlight the main literature themes and contributions. Methods: A search for the term 'poster presentation' was conducted simultaneously in 249 databases. Results were categorised by discipline and analysed by decade. The results were used to form an informetric‐based mapping review. Results: (i) Medicine and health care disciplines are the predominant poster users and since 1990 have accounted for 68–75% of the overall published data. (ii) Over 99% of the returns led only to abstract or title citations for conference posters. (iii) Poster presentations offer much potentially useful information, but remain difficult to access. Conclusions: If the aim of poster presentation is to share and discuss information with others, then the limitations of poster abstracts and questions raised in the retrieved literature suggest that further efforts are required to make this more effective. Library and information specialists of all disciplines are likely to play a key role in such developments, and especially those from the medicine and health care disciplines which feature so prominently.